Republic of Armenia : Technical Assistance Report-Strategic Choices for Tax Administration to Enhance Tax Compliance. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
This technical assistance report on Republic of Armenia advices on advises on strategic choices for tax administration and compliance risk management. It complements the March 2018 tax administration mission, which provided the State Revenue Committee (SRC) with general guidance to develop and implement a compliance improvement framework. Armenia's tax policy setting creates challenges for the SRC to effectively manage tax compliance. The Government's tax policy framework is likely to create new noncompliance opportunities and result in revenue leakages. Strengthened fundamental functions and processes are needed for the delivery of effective tax administration. Two issues raised in the 2018 tax administration mission report need to be highlighted again. The mission provided an analysis of SRC case selection and advised on the adoption of analytical tools to achieve better results. The SRC's current additive risk rule scoring approaches need to be supplemented by predictive modeling giving better predictions and prioritization of the likelihood and potential consequences of noncompliance-the use of such model is envisaged in the SRC's draft strategic plan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet